An Aanalysis of Illocutionary Acts in Thor: Love and Thunder Movie - Ardilla, Amoynindi Dewanti; Garnida, Susie Chrismalia (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
In communication, the speaker not only makes utterances but also conducts actions through those words. In addition to conveying information, individuals use language to perform actions that are intended to have a specific purpose and effect on the recipient. Actions carried out through spoken words are referred to as speech acts. The purpose of this research is to identify and describe the types and most dominant types of illocutionary acts that were presented in Thor: Love and Thunder movie through the movie and script. The researcher used the qualitative method to analyze the data. This research uses John Searle’s theory in Yule's books (1996) about various types of illocutionary acts including representative, directive, declarative, expressive, and commissive. The result of this study found a total of 97 data on illocutionary acts in Thor: Love and Thunder movie. First, the researcher found representative types (21 data) data, directive types (35 data), declarative types (5 data), expressive types (15 data), and commissive types (13 data). The most dominant type used in Thor: Love and Thunder is the directive type because Thor uses his words to command and lead his army.